Midgut serine proteinases participate in dietary adaptations of the castor (Eri) silkworm Samia ricini Anderson transferred from Ricinus communis to an ancestral host, Ailanthus excelsa Roxb - Kashung, Sochanngam; Bhardwaj, Parul; Saikia, Mahaswetta; Mazumdar-Leighton, Sudeshna (Frontiers in Insect Science, 2023)
Dietary change influenced the life-history traits, nutritional utilization, and midgut serine proteinases in the larvae of the domesticated polyphagous S. ricini, transferred from R. communis (common name: castor; family Euphorbiaceae; the host plant implicated in its domestication) to A. excelsa (common name: Indian tree of heaven; family Simaroubaceae; an ancestral host of wild Samia species). Significantly higher values for fecundity and body weight were observed in larvae feeding on R. communis (Scr diet), and they took less time to reach pupation than insects feeding on A. excelsa (Scai diet). Nevertheless, the nutritional index for efficiency of conversion of digested matter (ECD) was similar for larvae feeding on the two plant species, suggesting the physiological adaptation of S. ricini (especially older instars) to an A. excelsa diet. In vitro protease assays and gelatinolytic zymograms using diagnostic substrates and protease inhibitors revealed significantly elevated levels (p ≤ 0.05) of digestive trypsins, which may be associated with the metabolic costs influencing slow growth in larvae feeding on A. excelsa. RT-PCR with semidegenerate serine proteinase gene-specific primers, and cloning and sequencing of 3′ cDNA ends identified a large gene family comprising at least two groups of putative chymotrypsins (i.e., Sr I and Sr II) resembling invertebrate brachyurins/collagenases with wide substrate specificities, and five groups of putative trypsins (i.e., Sr III, Sr IV, Sr V, Sr VII, and Sr VIII). Quantitative RT-PCR indicated that transcripts belonging to the Sr I, Sr III, Sr IV, and Sr V groups, especially the Sr IV group (resembling achelase I from Lonomia achelous), were expressed differentially in the midguts of fourth instars reared on the two plant species. Sequence similarity indicated shared lineages with lepidopteran orthologs associated with expression in the gut, protein digestion, and phytophagy. The results obtained are discussed in the context of larval serine proteinases in dietary adaptations, domestication, and exploration of new host plant species for commercial rearing of S. ricini.